An Examination of the Impact of Government and Non-Profit Organization Relationship on Prisoner Advocacy and Services in Canada - Sokolov, Victor (Université d'Ottawa / University of Ottawa, 2014)
Drawing on themes emerging from semi-structured interviews, this study explores the relationship between the Government of Canada (GOC) and non-profit organizations (NPOs) operating in the punishment sector. The impact of this relationship on NPO advocacy is explored. It is argued that the GOC-NPO relationship creates a number of barriers for NPO advocacy, but NPOs manage to maintain this function through various forms of resistance. However, it was found that the majority of participating NPOs were coopted by the state through their extensive relationship with the GOC, and their service provision function in particular. It is therefore suggested that the majority of participating NPOs support the punishment system, making them a part of the Non-Profit Industrial Complex (NPIC).
Keywords: Non-profit organizations GOC; Prisoner advocacy